2015
DOI: 10.1175/jcli-d-15-0100.1
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo Singular Spectrum Analysis (SSA) Revisited: Detecting Oscillator Clusters in Multivariate Datasets

Abstract: Multichannel singular spectrum analysis (M-SSA) provides an efficient way to identify weak oscillatory behavior in high-dimensional data. To prevent the misinterpretation of stochastic fluctuations in short time series as oscillations, Monte Carlo (MC)-type hypothesis tests provide objective criteria for the statistical significance of the oscillatory behavior. Procrustes target rotation is introduced here as a key method for refining previously available MC tests. The proposed modification helps reduce the ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
75
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 100 publications
(76 citation statements)
references
References 47 publications
1
75
0
Order By: Relevance
“…In this context, Groth and Ghil (2015) found the Procrustes algorithm helpful in comparing the data eigendecomposition with that of the surrogate data generated by the red-noise null hypothesis, and showed that application of this algorithm substantially improves the explanatory power of the test. These authors further provided a rigorous mathematical extension of a composite null hypothesis test for M-SSA: for instance, a strong trend component can be excluded from the raw data when estimating the parameter of the null hypothesis.…”
Section: B Multivariate Singular Spectrum Analysis (M-ssa)mentioning
confidence: 99%
See 3 more Smart Citations
“…In this context, Groth and Ghil (2015) found the Procrustes algorithm helpful in comparing the data eigendecomposition with that of the surrogate data generated by the red-noise null hypothesis, and showed that application of this algorithm substantially improves the explanatory power of the test. These authors further provided a rigorous mathematical extension of a composite null hypothesis test for M-SSA: for instance, a strong trend component can be excluded from the raw data when estimating the parameter of the null hypothesis.…”
Section: B Multivariate Singular Spectrum Analysis (M-ssa)mentioning
confidence: 99%
“…This compression of the dataset into a few leading PCs is meant to reduce the computational costs of a subsequent M-SSA analysis (e.g., Dettinger et al 1995;Allen and Robertson 1996;Robertson 1996); see also Moron et al (1998) and Table 1 therein. Groth and Ghil (2015), though, have demonstrated possible negative effects of this variance compression on the detection rate of weak signals when the number of retained PCs becomes too small. In appendix B, we demonstrate that this practice can further affect negatively the judicious reconstruction of the spatio-temporal patterns of such weak signals, and recommend retaining a maximum number of PCs.…”
Section: B Multivariate Singular Spectrum Analysis (M-ssa)mentioning
confidence: 99%
See 2 more Smart Citations
“…However, to avoid any misinterpretation of random fluctuations as oscillations, we performed a Monte Carlo statistical test and compared the variance captured by each pair of ST-EOFs with that in a large ensemble of random-walk noise surrogates (Allen and Robertson 1996;Allen and Smith 1996;Groth and Ghil 2015). In this analysis, we considered 21 ST-EOF pairs.…”
Section: /40mentioning
confidence: 99%